1228. The Role of Procalcitonin (PCT) and Lactic Acid in Febrile Neutropenic Cancer Patients in an Oncological Emergency Center. (31st December 2020) - Chaftari, Patrick; Chaftari, Anne-Marie; Hachem, Ray Y; Yeung, Sai-ching; dagher, Hiba; Jiang, Ying; Malek, Alexandre; Mulonovich, Victor; Raad, Issam I; Raad, Issam I
Abstract: Background: Procalcitonin (PCT) and lactic acid have emerged as biomarkers that increase in bacterial infections/sepsis and have been used in conjunction with clinical judgment to guide antibiotic administration. The Multinational Association for Supportive Care in Cancer (MASCC) risk index has been used to classify the risk for patients with neutropenic fever. However this index includes subjective elements and complex metrics that make it difficult to use in an oncological emergency center (EC). The purpose of this study is to evaluate the role of serum PCT alone and in combination with lactate to predict bloodstream infections (BSI), hospitalization and 14 days mortality in febrile neutropenic cancer patients presenting to the EC. Methods: We conducted a retrospective study of all febrile neutropenic cancer patients who presented to our EC between April 1, 2018 and April 30, 2019 and had a serum PCT and lactic acid levels done. Fever was defined either as a documented temperature of ≥100.4 °F or a chief complaint of fever reported at home. Neutropenia was defined as an absolute neutrophil count ≤500 cells/mL. Results: We included 550 cancer patients of which 385 (70%) had hematologic malignancies and 165 (30%) had solid tumors. A BSI was documented in 116 (21%) patients due to gram negative organisms in 66%, gram positive organisms in 30%, and both in 4%. A higher rate of mortality within 14 days of EC presentation was seen in patients whose PCT ≥ 0.25 compared to those with PCT < 0.25 (5.2% vs 0.7%; p=0.002). Similarly a higher rate of BSI and a longer hospital stay was seen in patients whose PCT ≥ 0.25 compared to those with PCT < 0.25. A PCT ≥ 0.25 or a lactate level >2.2 had a sensitivity of 93% and a negative predictive value of 100% for a 14 day mortality. A logistic regression analysis showed an association between BSI and hematological malignancy, PCT ≥ 0.25, and lacate level >2.2 mmole/L. Conclusion: A PCT ≥ 0.25 was associated with BSI, LOS and 14 day mortality. The combination of PCT / serum lactate have a good sensitivity and high negative predictive value for BSI and mortality. Because this combination could be useful in identifying the high risk febrile patients requiring hospital admission, it will be compared to the standard but more labor intensive MASCC score index. Disclosures: Issam I. Raad, MD, Citius (Other Financial or Material Support, Ownership interest)Cook Medical (Grant/Research Support)Inventive Protocol (Other Financial or Material Support, Ownership interest)Novel Anti-Infective Technologies (Shareholder, Other Financial or Material Support, Ownership interest)